Health-Related Internet Use by Informal Caregivers of Children and Adolescents: An Integrative Literature Review - Park, Eunhee; Kim, Heejung; Steinhoff, Andreanna (JMIR Publications, 2016)
BackgroundInternet-based health resources can support informal caregivers who are caring for children or adolescents with health care needs. However, few studies discriminate informal caregivers' needs from those of their care recipients or those of people caring for adults. ObjectiveThis study reviews the literature of health-related Internet use among informal caregivers of children and adolescents. MethodsA total of 17 studies were selected from literature searches conducted in 6 electronic databases: PubMed, Cochrane, CINAHL, PsycINFO, ERIC, and EMBASE. All databases searches were limited to articles published in the years 2004 to 2014 in peer-reviewed publications. Search terms consisted of "health-related Internet use," "eHealth," "Internet use for health-related purpose(s)," "Web-based resource(s)," and "online resources," combined with informal caregiver (or "parents") of "child," "adolescent," "student," "youth," and "teen." The age range of the children receiving care was limited to younger than 22 years. Their informal caregivers were defined as persons (parents) who provided unpaid care or assistance to a child or an adolescent with health problems. ResultsAmong 17 empirical studies, the majority of informal caregivers of children with medical issues were the parents. Quantitative studies (14/17, 77%) reported prevalence and predictors of health-related Internet use, while mixed-methods and qualitative studies (3/17, 24%) investigated informal caregiver perceptions of helpful health-related Internet use and barriers of use. The prevalence of health-related Internet use varied (11%-90%) dependent upon how health-related Internet use was operationalized and measured. Disease-specific information was used for decision making about treatment, while social support via virtual communities and email were used for informal caregiver emotional needs. A digital divide of Internet access was identified in lower educated minorities. Most studies had methodological challenges resulting from convenience sampling, cross-sectional surveys, lack of theoretical frameworks, or no clear definitions of health-related Internet use. ConclusionsThis study provides an important understanding of how family members use Internet-based information and support systems during child caregiving. Healthcare providers and policy makers should integrate family needs into their current practices and policies. Further rigorous research is required to design efficient and effective nursing interventions.